Exploring Youth Political Participation: K-Pop Fan Activism in Indonesia and Thailand (Global Focus, 2021)
This paper explores K-pop fans political participation by looking at recent fan activism that happened in Indonesia and Thailand. Since the US fans participation in BLM campaign and ‘sabotaging’ of Trump’s Tulsa campaign rally, the K-pop fans community has made headlines on mainstream media as part of contemporary political discourse. Similar situation is also encountered in Southeast Asia where Korean popular culture has been consumed for decades and has large following. K-pop fans in Indonesia and Thailand have participated in various forms of activism supporting humanitarian causes through donations, criticizing new laws, or protesting against the government. Focusing on four key areas of analysis: the intersection between cultural and civic/political participation, the tension between participation and resistance, affect and collective identity, and impacts; this paper aims to explain how fandom may act as a powerful force that bridges cultural consumption and political participation amongst youths in the era of media convergence.